Emerging Trends in Cell and Gene Therapy - Danquah, Michael K.; Danquah, Michael K.; Mahato, Ram I.; Mahato, Ram I. (Humana Press : Imprint: Humana, 2013)
Examples from various organs and diseases illustrate the potential benefit obtained when both therapeutic approaches are combined with delivery strategies. Representing the combined effort of several leading international research and clinical experts, this book, Emerging Trends in Cell and Gene Therapy, provides a complete account on and brings into sharp focus current trends and state-of-the-art in important areas at the interface of cell- and gene-based therapies. This book addresses the current fragmented understanding regarding these two research areas and fills the vast unmet educational need and interest of both students and researchers in academia and industry.   Main features of the book: ·         Biological aspects of stem cell sources, differentiation and engineering.   ·         Application of microfluidics to study stem cell dynamics ·         Potential clinical application of stem cells and gene therapy to specific human disease. ·         Utilization of biomaterials and stem cells in regenerative medicine with particular emphasis on spinal cord repair, ligament and bone tissue engineering. ·         Biomimetic multiscale topography for cell alignment.